Mergers and acquisitions in Germany: Social-setting and regulatory framework - Frank A. Schmid; Mark Wahrenburg (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
The paper describes the legal and economic environment of mergers and acquisitions in Germany and explores barriers to obtaining and executing corporate control. Various cases are used to demonstrate that resistance by different stakeholders including minority shareholders, organized labour and the government may present powerful obstacles to takeovers in Germany. In spite of the overall convergence of European takeover and securities trading laws, Germany still shows many peculiarities that make its market for corporate control distinct from other countries. Concentrated share ownership, cross shareholdings and pyramidal ownership structures are frequent barriers to acquiring majority stakes. Codetermination laws, the supervisory board structure and supermajority requirements for important corporate decisions limit the execution of control by majority shareholders. Bidders that disregard the German preference for consensual solutions and the specific balance of powers will risk their takeover attempt be frustrated by opposing influence groups.
urn:nbn:de:hebis:30-10331
Keywords: G34; 330; Mergers and Acquisitions; German Corporate Governance System; Fusion; Übernahme; Regulierung; Kartellrecht; Corporate Governance; Deutschland